Fault Tolerant Control Multiprocessor Systems Modelling Using Advanced Stochastic Petri Nets. (2016) - Dumitrescu, Mariana
Abstract: Power systems need a safe management and power control. This means they are fault tolerant systems and specially need a strong safety of the processors, which have one of the most important tasks of the control. The paper presents how a processor can be modeled, what types of failures can appear in the functional state and the availability advanced modeling using discreet stochastic events models. The advanced Stochastic Petri Nets model proposed and used in this paper has a strong modeling power and this will be proved in comparison with classical availability models.